Dapatkah Anak Indonesia Diadopsi oleh Orang Asing Ditinjau dari Aspek Hukum Perdata Internasional - Arif, Rizal (Indonesian Journal of International Law, 2021)
International adoption of Indonesian child is a part of International Private Law matter, such as there was a case that is done by a white person who discovered by the police while taking 9 babies (one untul three months old) in the Airport of Kemayoran, Jakarta, which is suspected as babies trafficking. Or, there was the desire to do an Indonesian child legal adoption of wealthy Singaporean couple without knowing the procedure. The member of Babies trafficking fenomenont has been increasing since the economic crisis happened in July 1997 and the globalization era of free trade, where the border among States lessen (boarderless state). Due to the International Private Law, the writer tried to elaborate whether the Indonesian Child can be adopted by foreigners. If it is possible, which law may be used? Is it The Adoptant Law or the Adoptandus Law? If the Indonesian child may be adopted by the foreigners, what are the requirements? Considering the different law systems of international adoption between States, then how is the international community fort to handle the problem? And how does Indonesia handle this International Private Law problem?